β-Carboline monoterpenoid glucosides from Palicourea adusta - Valverde, Johnny (1999)
Lyaloside, a monoterpenoid glucoindole alkaloid, was isolated from the leaves of Palicourea adusta together with a mixture of its hydroxycinnamic acid derivatives, (E)-O-(6′)-cinnamoyl-4″-hydroxy-3″-methoxy-lyaloside and (E)-O-(6′)-cinnamoyl-4″-hydroxy-3″,5″-dimethoxy-lyaloside, which have been separated for the first time by high pressure liquid chromatography (HPLC). Their molecular weights were determined by HPLC electrospray ionization mass spectrometry (ESI-MS) and further identification of the structures was carried out by spectroscopic methods.